Synthetic ion-exchange resins: Soil and environmental studies - Skogley, Earl O.; Dobermann, Achim (Wiley, 1996)
The use of synthetic ion‐exchangers (commonly referred to as resins) to study natural media has steadily increased. These materials allow new and different ways to solve problems that cannot be resolved through usual approaches. A lack of knowledge or limited experience, however, has led to apparent confusion concerning appropriate use of resins for soil and environmental studies. The objective of this paper was to provide basic information on ion‐exchange resins, their physical and chemical properties, and to review how resins have been used to expand our understanding of soils and other environmental media. A review of the literature is presented as an aid to better understanding, and to provide additional sources for details concerning resin applications. A classification scheme for resin systems is presented, with the intent that it will assist in the development of more uniformity and comparability in the use of resins for soil and environmental studies. Applications of various systems and their limitations are discussed, including a system developed to provide universal adsorption of ions and bioavailability indexes from tests run either in the laboratory or in situ.